2006
DOI: 10.1017/s1138741600005977
|View full text |Cite
|
Sign up to set email alerts
|

Memories of the Terrorist Attacks of September 11, 2001: A Study of the Consistency and Phenomenal Characteristics of Flashbulb Memories

Abstract: In this study, I investigated students' memories of the terrorist attacks of September 11, 2001, carried out by Al Qaeda terrorists against the World Trade Center in New York and the Pentagon in Washington. Participants completed on two occasions (2 weeks and 8 months after the events took place) a memory questionnaire that included an assessment of the phenomenal richness of their memories. The results showed that the participants remembered very well the circumstances in which they first heard about the terr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…The dissociation between beliefs and accuracy is not uncommon (McCloskey et al, 1988;Neisser, 1982;Neisser & Harsch, 1992;Talarico & Rubin, 2003;Weaver, 1993;Wright, 1993) and many studies show that FBMs consistency is quite low, despite confidence and richness of details as measured by the total amount of recall (see Romeu, 2006). The novel result here is that the pattern of double dissociation between autobiographical/event memories and between consistency and confidence found by Coluccia et al (2006) was replicated for surprising episodes and extended to unsurprising ones.…”
Section: Dissociation Between Confidence and Consistencysupporting
confidence: 50%
“…The dissociation between beliefs and accuracy is not uncommon (McCloskey et al, 1988;Neisser, 1982;Neisser & Harsch, 1992;Talarico & Rubin, 2003;Weaver, 1993;Wright, 1993) and many studies show that FBMs consistency is quite low, despite confidence and richness of details as measured by the total amount of recall (see Romeu, 2006). The novel result here is that the pattern of double dissociation between autobiographical/event memories and between consistency and confidence found by Coluccia et al (2006) was replicated for surprising episodes and extended to unsurprising ones.…”
Section: Dissociation Between Confidence and Consistencysupporting
confidence: 50%
“…Several studies showed people in different cultures, including Turkey, had detailed recollections of how they heard about this event (Pezdek, 2003;Romeu, 2006;Tekcan, Ece, Gulgoz, & Er, 2003). The first was the terrorist attacks on the World Trade Center, on 11 September 2001, as a result of which approximately 3000 people died.…”
Section: The Eventsmentioning
confidence: 99%
“…This was undoubtedly one of the most devastating public events in recent history that had worldwide consequences. Several studies showed people in different cultures, including Turkey, had detailed recollections of how they heard about this event (Pezdek, 2003;Romeu, 2006;Tekcan, Ece, Gulgoz, & Er, 2003).…”
Section: The Eventsmentioning
confidence: 99%